The diagnosis of gynecological cancer in private practice - Jordan Massa, Fritz (2015)
There is no doubt that the cancer of the genital area is a constant concern today, making it the most common tumor that affects the lives of women. It is uterine carcinoma predominates and this one, which causes cervical higher mortality.